1989
DOI: 10.1080/00986448908940634
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design and Operation of Batch Processes

Abstract: The increased importance of high value-added specialty chemicals has stimulated interest in the development of better design and optimization methods for batch processes. These processes have a number of particular aspects (time-dependent behavior, discrete processing and structural alternatives) which make the development of optimal designs quite difficult. Five sets of decisions must be made to design a batch process. Because the entire problem is so complex, previous workers have focused on smaller, more ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…Moreover, this approach captures the influence of the variables that establish economic trade-offs between or among stages (Barrera and Evans, 1989) and the interactions among different product requirements. None of these effects can be taken into account with the constant factor model.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this approach captures the influence of the variables that establish economic trade-offs between or among stages (Barrera and Evans, 1989) and the interactions among different product requirements. None of these effects can be taken into account with the constant factor model.…”
Section: Discussionmentioning
confidence: 99%
“…A similar but simpler design problem has been presented by Olden-Ž . burg et al 2002 . The example is solved with the proposed MLDO formulation as well as with a MIDO solution technique.…”
Section: Illustrative Example Problemmentioning
confidence: 99%
“…Define as the perturbation about the nominal vector . Then, the control trajectory is (2) It is desirable to define an uncertainty representation that is general enough to include the uncertainty descriptions common in practice. This can be done using the Hölder -norm [28] defined for a general vector by…”
Section: A Uncertainty Descriptionmentioning
confidence: 99%
“…The model-based computation of optimal control policies for batch and semibatch processes is of increasing interest due to industrial interest in improving productivity [2], [6], [17], [40]. However it has been shown that all of the benefits of using optimal control can be lost with subtle variation in either the model parameters or in the performance of the feedback controller to track the optimal setpoint trajectory [16], [41], [44].…”
mentioning
confidence: 99%